On the heterogeneous effect of trade on unemployment - Céline Carrère; Marco Fugazza; Marcelo Olarreaga; Frédéric Robert-Nicoud (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
We embed a model of the labor market with sector-specific search-and-matching frictions into a Ricardian model with a continuum of goods to show that trade reduces unemployment in countries with comparative advantage in sectors with more efficient labor markets and leads to higher unemployment in countries with comparative advantage in sectors with less efficient labor markets. We test this prediction in a panel dataset of 107 countries during the period 1995-2009 and find that the data supports the theoretical prediction. Our results also help reconciliate the apparently contradicting evidence in the empirical literature on the impact of trade on unemployment.
Keywords: 330; Trade; Search unemployment